Use of a mixed culture strategy to isolate halophilic bacteria with antibacterial and cytotoxic activity from the Manaure solar saltern in Colombia - Conde-Martínez, Natalia (BMC Microbiol, 2017)
BACKGROUND: Water evaporation in solar salterns creates salinity gradients that promote the adaptation of microbial species to different salinities. This competitive habitat challenges the metabolic capabilities of microorganisms and promotes alterations in their production of secondary metabolites. Thus, solar salterns are a potentially important source of new natural products. In Colombia, the most important and representative solar saltern is located in Manaure (La Guajira) in the north of Colombia. The aim of this study was to develop an alternative screening strategy to select halophilic bacteria as producers of bioactive compounds from mixed microbial cultures rather than individual environmental isolates. Brine and sediment samples from different ponds (across a salinity gradient) were inoculated in seven different culture media to grow bacteria and archaea, allowing for a total of 40 different mixed cultures. An organic extract from each mixed culture was obtained and tested against multidrug resistant pathogens, including Klebsiella pneumoniae, vancomycin-resistant Enterococcus faecium, methicillin-resistant Staphylococcus aureus and Bacillus subtilis. In addition, the extracts were tested against two human cancer cell lines, cervical adenocarcinoma (SiHa) and lung carcinoma (A-549). RESULTS: Twenty-four of the forty extracts from mixed cultures obtained from brine and sediment samples from the Manaure solar saltern showed antibacterial activity against Bacillus subtilis. Two extracts, referred to as A1SM3–29 and A1SM3–36, were also active against a methicillin-resistant Staphylococcus aureus, with the latter extract also showing slight cytotoxic activity against the assayed human lung cancer cell line. From this mixed culture, nine isolates were cultivated, and their extracts were tested against the same pathogens, resulting in the identification of a Vibrio sp. strain (A1SM3–36-8) with antimicrobial activity that was similar to that observed for the mixed culture extract. The extract of this strain was subjected to a bioautography assay, and 3 different fractions exhibited antibacterial activity against methicillin-resistant Staphylococcus aureus. Based on the amount obtained for each fraction, F3 was selected to isolate and identify its metabolites. The major compound was identified by NMR and HRMS as 13-cis-docosenamide, an amide that has been previously reported to be an antimicrobial and cytotoxic compound. CONCLUSIONS: Our results shows the utility of our strategy in detecting bioactive molecules in initial mixed cultures by biological assays, resulting in the isolation and characterization of Vibrio sp. A1SM3–36-8, a halophilic strain with great antibacterial and cytotoxic potential. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12866-017-1136-x) contains supplementary material, which is available to authorized users.